تأثير الحجم الحبيبي على بعض الخواص الميكانيكية لمواد متراكبة بوليمرية متدرجة وظيفيا مصنعة بطريقة الترسيب تحت تأثير الجاذبية - عواد هلوش خضر; زينب حازم حميد الخفاف (Journal of Engineering and Sustainable Development, 2019)
This research includes a Functionally Graded Polymeric Composite )FGPCs). These Composites were fabricated from unsaturated polyester resin as a matrix reinforced with silicon carbide particles) SiCp) of different particle size ) 53,106,150 µm) and )6 vol%) bulk volume fraction produced by Gravity Casting and room temperature )22°C) and produced sample from pure polyester to use it in comparison. The aim of the present research is to study the effect of the change in )SiCp) particle size on the local value of volume fraction, hardness, and Youg modulus at specific points along with the graded samples, and graded samples were cut to nine portions with thickness )8mm) and density, bulk volume fractions were calculated, then and tensile test. Results show that local values of volume fraction, hardness and Young modulus decreased in pure end samples and increased in lower end samples because increased particles SiCp in this position.